2017
DOI: 10.1002/aet2.10053
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Physician Training on Mild Traumatic Brain Injury: A Systematic Review

Abstract: Objectives: Mild traumatic brain injury (mTBI) is the most common emergency department (ED) brain injury presentation worldwide. Despite its frequency, practice variation and care gaps exist among emergency physicians (EPs) in diagnosing and appropriately managing mTBI in the ED. The objective of this review was to identify mTBI-specific training undertaken to improve the detection and management of mTBIs by EPs and its impact on practice.Methods: A comprehensive search strategy utilized four bibliographic dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…In a systematic review of studies addressing mTBI training resources available to EM providers, investigators highlighted the limited attention that mTBI receives, resulting in variation across mTBI management. 19 In addition, our findings demonstrate that the types of discharge instructions provided were variable based on provider preference, rather than department standard. Finally, the selected ICD-9 or ICD-10 codes may not have captured every patient who presented with mTBI symptoms.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…In a systematic review of studies addressing mTBI training resources available to EM providers, investigators highlighted the limited attention that mTBI receives, resulting in variation across mTBI management. 19 In addition, our findings demonstrate that the types of discharge instructions provided were variable based on provider preference, rather than department standard. Finally, the selected ICD-9 or ICD-10 codes may not have captured every patient who presented with mTBI symptoms.…”
Section: Discussionmentioning
confidence: 77%
“…First, this variability may be because of a knowledge gap among EM providers. In a systematic review of studies addressing mTBI training resources available to EM providers, investigators highlighted the limited attention that mTBI receives, resulting in variation across mTBI management 19 . In addition, our findings demonstrate that the types of discharge instructions provided were variable based on provider preference, rather than department standard.…”
Section: Discussionmentioning
confidence: 78%
“…The Sports Concussion Assessment Tool 3 (SCAT3) is an assessment of concussion symptomatology that is sometimes used to assist with concussion diagnosis in the ED, as there is no ED specific concussion tool. [7][8][9][10][11][12][13] The SCAT3 was developed for sports and is a sensitive test of postconcussion symptoms in athletes. 6,8,[14][15][16][17][18][19][20] The SCAT3 includes a cognitive screen, a postural stability test, and a symptom evaluation (SE).…”
Section: E303mentioning
confidence: 99%
“…It has been reported that the rates of concussion are rising year on year, however this may be attributable to increased awareness of the condition by clinicians and the public, particularly through educational efforts (7)(8)(9). Many patients will recover from a concussion within 10 days; however, reports suggest that 10-15% will develop persistent symptoms beyond 4 weeks (10). Persisting concussion symptoms can include: headaches, fatigue, changes in mental health (e.g.…”
Section: Introductionmentioning
confidence: 99%